Pseudoaneurysm of the Anterior Tibial Artery following Ankle Arthroscopy in a Soccer Player - Ichiro Tonogai; Tetsuya Matsuura; Toshiyuki Iwame; Keizo Wada; Tomoya Takasago; Tomohiro Goto; Daisuke Hamada; Yohei Kawatani; Eiki Fujimoto; Tetsuya Kitagawa; Shyoichiro Takao; Seiji Iwamoto; et al. (Case Reports in Orthopedics)
Ankle arthroscopy carries a lower risk of vascular complications when standard anterolateral and anteromedial portals are used. However, the thickness of the fat pad at the anterior ankle affords little protection for the thin-walled anterior tibial artery, rendering it susceptible to indirect damage during procedures performed on the anterior ankle joint. To our knowledge, only 11 cases of pseudoaneurysm involving the anterior tibial artery after ankle arthroscopy have been described in the literature. Here we reported a rare case of a 19-year-old soccer player who presented with pseudoaneurysm of the anterior tibial artery following ankle arthroscopy using an ankle distraction method and underwent anastomosis for the anterior tibial artery injury. Excessive distraction of the ankle puts the neurovascular structures at greater risk for iatrogenic injury of the anterior tibial artery during ankle arthroscopy. Surgeons should look carefully for postoperative ankle swelling and pain after ankle arthroscopy.